Interacting Abiotic Factors Affect Growth and Aflatoxin B1 Production Profiles of Aspergillus flavus Strains on Pistachio-Based Matrices and Pistachio Nuts - Baazeem, Alaa; Garcia-Cela, Esther; Medina, Angel; Magan, Naresh (Frontiers in Microbiology, 2021)
Pistachio nuts are an economically important commodity produced by many countries. They can be colonized by mycotoxigenic fungi, especially Aspergillus flavus, resulting in contamination with aflatoxins (AFs), especially aflatoxin B1 (AFB1), a Class 1a carcinogen. The objectives were to examine the effect of interactions between the two key abiotic factors, temperature and water activity (aw) on (a) in vitro growth and AFB1 production by four strains of A. flavus isolated from pistachio nuts, on a milled pistachio nut medium modified ionically (NaCl) and non-ionically (glycerol) in the range 20-35oC and 0.995 to 0.85 aw, (b) colonization of layers of raw pistachio nuts stored at different interacting temperature x aw conditions and on relative AFB1 production and (c) develop models to produce contour maps of the optimal and marginal boundary conditions for growth and AFB1 production by up to 4 strains of this species. On pistachio nut-based media, optimum growth of four strains of A. flavus was at 0.98-0.95 aw and 30-35°C. Optimum AFB1 production was at 30-35°C and 0.98 aw. No significant differences in growth was found on ionic and non-ionically modified media. Colonisation of layers of raw pistachio nuts was slower and contamination with AFB1 significantly less than in in vitro studies. Contour maps based on the pooled data for up to four strains (in vitro, in situ) showed the optimum and marginal conditions for growth and AFB1 production. These data can be used to identify those conditions which represent a high, intermediate or low risk of colonisation and AFB1 contamination in the pistachio nut processing chain. These results are discussed in the context of the development of appropriate intervention strategies to minimise AFB1 contamination of this economically important commodity.